2022
DOI: 10.1016/j.isci.2021.103726
|View full text |Cite
|
Sign up to set email alerts
|

High nitrogen in maize enriches gut microbiota conferring insecticide tolerance in lepidopteran pest Spodoptera litura

Abstract: Summary Abuse of chemical fertilizers and insecticides has created many environmental and human health hazards. We hypothesized that high nitrogen (N) in crops changes insect gut microbiota leading to enhanced insecticide tolerance. We investigated the effect of high N in maize on gut microbiota and insecticide tolerance of the polyphagous pest Spodoptera litura . Bioassays showed that high N applied in both maize plants and artificial diets significantly enhanced larval growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…Notably, the type of diet, host plant, season, population density, and geographic position influence gut bacterial diversity [53]. Feeding can change the gut microbiota community of lepidopteran insects [52,54]. For instance, mulberry leaves are primarily composed of xylan (10-40%) and cellulose (19-25%), which shows the importance of intestinal microbes for food digestion in silkworms [55].…”
Section: Diversity Of the Lepidopteran Gut Microbiotamentioning
confidence: 99%
“…Notably, the type of diet, host plant, season, population density, and geographic position influence gut bacterial diversity [53]. Feeding can change the gut microbiota community of lepidopteran insects [52,54]. For instance, mulberry leaves are primarily composed of xylan (10-40%) and cellulose (19-25%), which shows the importance of intestinal microbes for food digestion in silkworms [55].…”
Section: Diversity Of the Lepidopteran Gut Microbiotamentioning
confidence: 99%
“…With the advent of penicillin, antibiotics have been widely used clinically with significant anti-infective effects, but while antibiotics have therapeutic effects, they are also accompanied by many adverse reactions. Hu et al [6] believed that there are five major hazards of the abuse of antibiotics through comprehensive analysis, the first is the harm to patients. Renal toxicity-The abuse of antibiotics can induce drug-induced renal failure, manifested as proteinuria, hematuria, etc., and in severe cases, azotemia can occur, resulting in decreased renal function [7] ; hepatotoxicity-Drugs cause liver damage through direct damage or allergic mechanisms; the abuse of antibiotics can destroy the normal bacteria in the human body, leading to a double infection; ototoxicity-The abuse of antibiotics can damage to vestibular function and auditory nerves, resulting in vision loss, nystagmus, nausea, vomiting and ataxia, hearing loss and even permanent deafness [8] ; gastrointestinal reaction-Nausea, vomiting, abdominal pain, diarrhea and constipation reactions, toxic reactions, low immunity [9] ; blood toxicity-Red blood cells, white blood cells, platelet blood reduction and even cause hemolytic anemia, aplastic anemia, etc., [10] ; Secondly, the abuse of antibiotics can lead to the emergence of super-resistant bacteria; thirdly, the abuse of antibiotics poses a threat to clinical practice; fourth, the abuse of antibiotics wastes resources; fifth, the antibiotics exist in sewage in an active form, destroying the ecological balance.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that gut microbiota can enhance insecticide resistance ( Kota et al, 2021 ; Hu et al, 2022 ). Inoculation of Spodoptera litura larvae with E. mundtii and Enterococcus casseliflavus significantly reduced susceptibility to methomyl ( Hu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that gut microbiota can enhance insecticide resistance ( Kota et al, 2021 ; Hu et al, 2022 ). Inoculation of Spodoptera litura larvae with E. mundtii and Enterococcus casseliflavus significantly reduced susceptibility to methomyl ( Hu et al, 2022 ). In Cletus punctiger , the gut commensal bacterium Burkholderia can degrade organophosphate compounds and remarkably increase the resistance against fenitrothion ( Kota et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%